2000
DOI: 10.1073/pnas.97.1.371
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous peptide immunization via corneum barrier-disrupted murine skin for experimental tumor immunoprophylaxis

Abstract: H-2K b -restricted tumor epitope peptides, including tyrosinase-related protein 2 residues 181-188 (TRP-2) and connexin 37 residues 52-59 (MUT1), were applied to permeability barrier-disrupted C57BL͞6 (B6) mouse skin from which the stratum corneum of the epidermis had been removed by tape-stripping. This procedure primed tumor-specific cytotoxic T lymphocytes (CTLs) in the lymph nodes and spleen, protected mice against subsequent challenge with corresponding tumor cells, and suppressed the growth of establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 42 publications
2
85
0
Order By: Relevance
“…46,[48][49][50] An additional advantage is that physical barrier disruption itself has been shown to trigger activation of keratinocytes and LCs in skin, providing some level of 'built-in' adjuvant response. [44][45][46][49][50][51][52] We thus tested a model where the dorsal ears of anesthetized mice were tape-stripped followed by application of as-assembled, airdried (Poly-1/ova) 40 films on either glass or PDMS substrates, fixed in place by surgical tape against the exposed ear skin, mimicking a common strategy used in skin vaccination studies 45,46 (Figure 1a). Tape-stripping reproducibly removed significant portions of the SC but did not disrupt the viable epidermis, as assessed by histology ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…46,[48][49][50] An additional advantage is that physical barrier disruption itself has been shown to trigger activation of keratinocytes and LCs in skin, providing some level of 'built-in' adjuvant response. [44][45][46][49][50][51][52] We thus tested a model where the dorsal ears of anesthetized mice were tape-stripped followed by application of as-assembled, airdried (Poly-1/ova) 40 films on either glass or PDMS substrates, fixed in place by surgical tape against the exposed ear skin, mimicking a common strategy used in skin vaccination studies 45,46 (Figure 1a). Tape-stripping reproducibly removed significant portions of the SC but did not disrupt the viable epidermis, as assessed by histology ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Epicutaneous or transmucosal immunization with protein and peptides has been reported to be efficient in inducing IFN-␥ production and cytotoxicity in T cells (38), especially when combined with inflammatory stimuli like tape stripping, cholera toxin, and Toll-like receptor ligands, such as oligonucleotides and imiquimod (16)(17)(18)(19). Seo et al (16) showed that LCs from tape-stripped skin are activated and express higher levels of costimulatory molecules and MHC-class I. When these LCs were peptide pulsed, they were able to induce cyotoxicity in CD8 ϩ T cells, indicating that they might be involved in this process (16).…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al (16) showed that LCs from tape-stripped skin are activated and express higher levels of costimulatory molecules and MHC-class I. When these LCs were peptide pulsed, they were able to induce cyotoxicity in CD8 ϩ T cells, indicating that they might be involved in this process (16). However, this was not formally proven, and therefore, the precise role of LCs still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] TS leads to removal of the outermost horny layer of the skin, resulting in enhanced permeability and maturation and activation of LCs via inflammatory cytokines secreted from keratinocytes. 11,12 The barrier function of the SC can also be bypassed by hydration of the skin, which leads to swelling of the keratinocytes and pooling of fluid into intercellular spaces. This kind of pretreatment of the skin leads to development of humoral 13,14 and Th responses after TCI with proteins or peptides.…”
mentioning
confidence: 99%